CLASSIFICAÇÃO DOS SERES VIVOS: UMA PROPOSTA DE AULA EXPERIMENTAL NO CONTEXTO DA ALFABETIZAÇÃO CIENTÍFICA - Araújo Borges, Karen; Lourenção, Bruna Cláudia; Pereira Caetano, Larissa; Rodrigues Borges, Luz Clarita; Abadia de Sousa Alves, Milena (Intercursos, 2026)
não há